The Mirror, the Self(ie) and the New Sacred. Bodies, Objects, and Figures of the Contemporary "Cult of the Self" - Simona Stano (Ocula)
This paper investigates the "cult of the Self" pervading contemporary mediatised cultures, adopting a semiotic approach. More specifically, it draws on the analysis of the fictional case of Ionismo, ironically represented by director Alessandro Aronadio in the movie Just Believe (orig. IO C'È, 2018), to shed new light on the figure of the "influencer", which has become fundamental in contemporary mediascapes. Thus it problematises the bodies, as well as the sacred objects, and more generally the figures, of today's cult of the Self, with specific reference to the "generative model" suggested by Just Believe, as well as to the understanding of the sacred in the "postsecular" era.